Forest Carbon Sink Evaluation – An Important Contribution for Carbon Neutrality. Issue 1 (July 2021) - Chen, Keren; Cai, Qiyuan; Zheng, Nan; Li, Yinan; Lin, Changyong; Li, Yuanfei
Abstract: Forest carbon sink refers to the carbon storage in nature, including the process, activity and mechanism of removing carbon dioxide from the air. Forest carbon sinks play a very important role in reducing the concentration of greenhouse gases in the atmosphere and slowing down the global warming process. Fujian Province is one of the key forest areas in southeast China. It has a mild climate, abundant rainfall, superior natural conditions, and abundant forest resources. According to the National Forest Resources Continuous Inventory Statistics, the Fujian forest coverage rate reached 66.8% in 2018 and has kept the No. 1 ranking in China for the past 40 consecutive years. The potential of forest carbon sink resources is considerable. This article first analyzes forest carbon sinks and their advantages, and then studies the development of forest carbon sinks in Fujian Province, and carries out quantitative estimation. Finally, relevant suggestions for the development of forest carbon sinks are given.